ATRT-17. A phase II study of continuous low dose panobinostat in paediatric patients with malignant rhabdoid tumours and atypical teratoid rhabdoid tumours. (3rd June 2022) - Wood, Paul; Desai, Jayesh; Waldeck, Kelly; Cain, Jason; Gottardo, Nicholas; Strong, Robyn; Kinross, Kathryn; Carr, Michelle; Jones, Janelle; Wong, Lily; Ziegler, David; Hansford, Jordan; et al.
Abstract: BACKGROUND: Panobinostat treatment has been shown to terminally differentiate malignant rhabdoid tumours (MRT) and atypical teratoid rhabdoid tumours (ATRT) in pre-clinical models. We report results of the open label, phase II study of oral panobinostat in patients with newly diagnosed or relapsed MRT/ATRT. AIMS: To assess the anti-tumour activity of low dose, continuous oral panobinostat as well as its associated toxicities. To assess the biological activity of low dose panobinostat by measuring histone H4 acetylation status in peripheral mononuclear cells (PMNC), and differentiation markers. METHODS: Following primary institutional standard of care induction and consolidation chemotherapy and/or radiation treatment, patients were enrolled and commenced on panobinostat as a continuous daily oral dose starting at 10mg/m 2 /day, with a three-week wash out period between therapies. Real-time acetylation status, measuring acetylated H4 on PMNC, was performed to determine the pharmacodynamics of panobinostat at different dosing levels. Patients were monitored for toxicity; dose reductions were in decrements of 2mg/m 2 /day. RESULTS: A total of 13 patients with newly diagnosed ATRT/MRT and one patient with relapsed MRT have been enrolled. The average age at enrollment was 3.6 years (range 0.8-6.8 years). The mean treatment duration was 206 days (13-344 days). Currently, six patients (42.9%) remain on study with a mean study duration of 531 days (range 13-895 days). 6/14 patients (42.9%) were removed due to disease progression at a mean study duration of 245 days (44-560 days). 2/14 patients (14.3%) withdrew due to toxicity. 12/14 patients (85.7%) required dose reductions. The main toxicities were thrombocytopaenia and leukopaenia (Grade III-IV). Real-time pharmacodynamic assessment of panobinostat, at a dose as low as 6mg/m 2 /day resulted in significant acetylation of histone H4 in PMNC. CONCLUSIONS: Treatment with low dose panobinostat is well tolerated in infants and children with MRT/ATRT, with significant acetylation of histone H4 in PMNC.